Swelling induced regeneration of TiO2-impregnated chitosan adsorbents under visible light. (20th April 2016) - Yang, Limin; Jiang, Lei; Hu, Di; Yan, Qingyun; Wang, Zhi; Li, Sisi; Chen, Cheng; Xue, Qi
Highlights: Swelling of polysaccharide induced photosensitization is first reported. Regeneration of chitosan-based adsorbent beads is achieved under visible light. The adsorbed dye pollutants are photodegraded during regeneration process. The adsorbability is mostly recovered after six regeneration cycles. Abstract: Since only the molecules that are in direct contact with the TiO2 surface undergo photosensitization, it is challenging to regenerate the TiO2 -impregnated chitosan (TIC) adsorbent beads under visible light. This study focused on the role of chitosan swelling properties. It was found that dye-loaded TIC adsorbent exhibited a pH-dependent swelling owing to protonation/deprotonation of free amino groups on chitosan chains. In the acidic medium (pH < 6.0), the adsorbent underwent a 'smart' phase transition from a dry contracted state to a hydrated swollen state, and its physicochemical properties were also significantly changed, which eventually enabled the photosensitized oxidation of dye. This swelling induced regeneration was further confirmed by Fourier transform infrared (FT-IR) spectroscopy and X-ray photoelectron spectroscopy (XPS). The involvement of oxygen radical species (O2 − /HOO and OH) was also confirmed with electron spin resonance (ESR) spectroscopy. Moreover, the adsorption effectiveness of TIC adsorbent was mostly recovered after six regeneration cycles.